(untitled) (AYUSHDHARA, 2016)
Arsha is one of the prime important disease from Asthamahagada, a group of disease which is to be treated with great difficulty. Arsha is the gift of busy life style with main etiological factor Mithyaaahar-vihar. In modern medical science many techniques like sclerotherapy, cryosurgery, Rubber band ligation, Infrared photo coagulation, Laser therapy, stapled haemorrhoidectomy, Open haemorrhoidectomy etc. are in practice where in the result was found to be in less satisfactory. In this regard to determine a solution for satisfactory cure, the Ksharasutra ligation method in Arsha was studied. In the present study the Apamarga ksharasutra ligation was done on different sizes, shapes and degrees of Arsha. Apamarga ksharasutra was prepared as per standard method described in Ayurvedic texts. A total of 30 patients were selected by simple random sampling method with the complaints of Vibhanda, Raktasrava, Kandu, Pandu. The study revealed the better result of Ksharasutra ligation .It was found that Ksharasutra ligation procedure of Arsha is better alternative because of advantages like minimum hospital stay, no bleeding during or after operation, more acceptability, low cost effective, no post-operative complications etc. Statistically, Ksharasutra ligation for Arsha was found to be highly significant and effective treatment. No adverse effects were noted during follow up period.